Yakut Emigration: Features of Adaptation and Communication - E. P. Antonov (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The issues of adaptation of Yakut emigrants forced to escape the revolution, the Civil War and the Gulag to different countries are considered. The role of Yakut emigrants in the preservation of national-cultural identity is described. Their participation in the civilizational dialogue between East and West is emphasized. A classification of the stages of the formation of local groups and microgroups of Yakut emigrants in the countries of the world is suggested. The approximate number, composition and territorial distribution of Yakut emigrants in China (the central group), Japan (southern Sakhalin), Finland, and the presence of microgroups in the USA and Australia are established. Attention is paid to the specifics of interaction of Yakut emigrants in the absence of a registered organization through communication, in which organizational, ideological, material activities were carried out. It is proved that correspondence was carried out in Russian, English, and various transcriptions of the Yakut script were used: Bötlingkowski, Novgorodovski, Cyrillic. Particular attention is paid to the high mobility of the Yakut emigrants, their desire to master new languages, qualifications and education for successful adaptation abroad. It is concluded that the Yakut emigrants failed to form a mechanism for the reproduction of ethnic identity (language, culture) in a foreign land. It was established that there was no organized opposition to repatriation by Yakut emigrants, but all returnees were unreasonably repressed by the NKVD.